Integrated Logistics Information for Supply Chain Management Optimization in the E-Commerce Industry - N. Nurani; Abd. Rajab (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to examine the role of integrated logistics information in optimizing supply chain management within the e-commerce industry. Adopting a qualitative research approach based on a systematic literature study, this research synthesizes prior theoretical and empirical studies to develop a comprehensive understanding of how logistics information integration supports efficiency, coordination, and responsiveness in e-commerce supply chains. The analysis draws on peer-reviewed journal articles and authoritative sources to identify recurring patterns, key dimensions, and emerging trends related to digital logistics integration. The findings indicate that integrated logistics information significantly enhances supply chain visibility, operational efficiency, service performance, and agility, while also supporting resilience and sustainability objectives. Furthermore, the study reveals that the effectiveness of integration depends on technological readiness, data quality, organizational alignment, and inter-organizational collaboration. The main contribution of this research lies in positioning integrated logistics information as a strategic capability that underpins supply chain optimization in dynamic e-commerce environments and provides a foundation for sustainable and resilient supply chain development.